2014
DOI: 10.1136/bmjopen-2014-005025
|View full text |Cite
|
Sign up to set email alerts
|

A coronary heart disease prediction model: the Korean Heart Study

Abstract: ObjectiveThe objectives of this study were to develop a coronary heart disease (CHD) risk model among the Korean Heart Study (KHS) population and compare it with the Framingham CHD risk score.DesignA prospective cohort study within a national insurance system.Setting18 health promotion centres nationwide between 1996 and 2001 in Korea.Participants268 315 Koreans between the ages of 30 and 74 years without CHD at baseline.Outcome measureNon-fatal or fatal CHD events between 1997 and 2011. During an 11.6-year me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
134
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 17 publications
(26 reference statements)
2
134
1
Order By: Relevance
“…Prior studies show that FRS tends to overestimate coronary risk in Asian populations. 21 Despite this limitation, this registry is the largest databank with regard to the use of CACS and the utility of its addition to FRS in an Asian population with a relatively long follow-up duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies show that FRS tends to overestimate coronary risk in Asian populations. 21 Despite this limitation, this registry is the largest databank with regard to the use of CACS and the utility of its addition to FRS in an Asian population with a relatively long follow-up duration.…”
Section: Discussionmentioning
confidence: 99%
“…4, 21 Thus, in an effort to improve risk assessment in varying populations, it is recommended to explore alternative risk markers additional to FRS. To this end, CACS appears to be a useful adjunct to FRS when assessing cardiovascular risk, because CACS typically reflects atherosclerotic plaque burden in the coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The FRS has been adapted for the prediction of cardiovascular event risk worldwide [15,16]. Although FRS is being used as a valuable tool for cardiovascular risk assessment, general extrapolation of this algorithm to various ethnicities or races may misclassify CAD risk in as much as the FRS was predominantly established based on a Caucasian population [17,18]. To this end, several previous studies have examined multiple ethnic or racial groups in an effort to test the utility or validity of the FRS.…”
Section: Rationale Behind the Koica Registrymentioning
confidence: 99%
“…To this end, several previous studies have examined multiple ethnic or racial groups in an effort to test the utility or validity of the FRS. Several investigators have demonstrated the overestimation of cardiovascular risk when FRS was directly applied to other ethnicities, such as in Asia including South Korea and several countries in Europe [17][18][19][20][21][22]. In a study based on a Korean population, the investigators reported that FRS overestimated CAD risk and CAD incidence was low [18].…”
Section: Rationale Behind the Koica Registrymentioning
confidence: 99%
“…To evaluate the degree of arteriosclerosis we performed PWV and ABI. Blood vessel elasticity is studied by aortic PWV, whereas ABI can evaluate the degree of angiostenosis or occlusion by calculating both humerus and ankle pressure [16,17]. Thus, the risk of cardiovascular diseases can be evaluated by the conditions of these vessels [18,19].…”
Section: Metabolic Syndrome and Dyslipidemia Arteriosclerosis Evalutionmentioning
confidence: 99%